The role of acoustic radiation force impulse elastography in the differentiation of benign and malignant focal liver masses - Akdoğan, Emin; Gelebek Yılmaz, Feyza (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: The aim of this study was to evaluate elasticity of benign and malign focal liver lesions and surrounding parenchyma as measured by acoustic radiation force impulse (ARFI). Materials and Methods: 34 hemangiomas, 4 focal nodular hyperplasia (FNH), 10 hepatocellular carcinoma (HCC) and 22 metastatic lesions from a total of 62 patients were examined with ARFI elastography. ARFI measurements for each tumor type were expressed as mean ± standard deviation for liver mass and surrounding parenchyma. ARFI values were compared between tumor types and surrounding parencyhma. Results: The mean stiffness values were 2.15±0.73 m/s for hemangiomas (n=34), 3.22±0.18 m/s for FNH (n=4), 2.75±0.53 m/s for HCC (n=10) and 3.59±0.51 m/s for metastasis (n=22). Although there was not a significant difference between hemangiomas and HCC lesions in ARFI values (p>0.05), hemangiomas showed significantly different ARFI values from FNH and metastases (p<0.05). Also, there were significant differences in ARFI values between malignant and benign masses. The area under the receiver-operating characteristics curves for discriminating the malignant from benign liver masses was 0.826 (p<0.001). An ARFI value of 2.32 m/s was selected as cut-off value to differentiate malignant liver masses from benign ones (sensitivity: 0.93, specificity: 0.60). Conclusion: Although currently ARFI is not a definitive method for the primary diagnosis of focal solid liver lesions, it provides additional important information non-invasively for differential diagnosis. Cite this article as: Akdoğan E, Gelebek Yılmaz F. The role of acoustic radiation force impulse elastography in the differentiation of benign and malignant focal liver masses. Turk J Gastroenterol 2018; 29: 456-63.